Risk Factors For Infection In Orthopedic Division Patients at Tishreen University Hospital - جوني, أحمد; يازجي, هيثم; صقر, كنان (Latakia University Journal -Medical Sciences Series, 2020)
Background: Surgical site infection (SSI) is one of the most important problems facing the orthopedic surgeon. Surgical site infection is an important prognostic factor that plays a major role in the progression of the case. This study was undertaken to evaluate the risk factors responsible for SSI and to determine the preventive measures for SSI. Patients and Methods: This study compromised all the hospitalized patients in the Orthopedic Division in Tishreen University Hospital during 2018. This study analyzed 418 patients and studied the risk factors for the development of SSI and then categorized patients into two groups according to the development of infection (with and without). Results: Infection has been developed in 42 patients (10%). In statistical analysis, we have found that open fractures were associated with infection (OR:10, 95% CI 4.8-20.9, p=0.0001), chronic kidney disease (OR:5.7, 95% CI 3.1-11.2, P=0.03), Internal fixation (OR:4.8, 95% CI 2.8-9.4, P=0.03), shaving in the patient room (OR:4.29, 95% CI 2.1-8.3, P=0.01), diabetes mellitus (OR:3.8, 95% CI 1.9-7.5, P= 0.002), more than 2 hours surgery (OR:2.8, 95% CI 5.7-10.6, P=0.03), emergency stretcher (OR:2.4, 95% CI 1.2-4.6, P=0.02), Emergency Operating Room (OR:2.05, 95% CI 1.1-3.5, P=0.01), and lower limb (OR:2, 95% CI 1.1-3.2, P=0.04). Conclusion: Open fractures, chronic kidney disease, Internal fixation, shaving in the patient room, diabetes mellitus, more than 2 hours surgery, emergency stretcher, Emergency Operating Room and lower limb each was an independent risk factor for the developing of SSI in the orthopedic division.